The Assessment of Risks and Cost-Effectiveness of Resource-Saving and Environmentally Sound Innovative Water Desalination Projects - Yulia Alexandrovna NAZAROVA; Natalia Sergeevna SHCHERBAKOVA; Alena Sergeevna KINDRASHINA; Ivan Olegovich GORUNOV (Communications of International Proceedings, 2021)
In their paper, the authors propose some complementary methods for conventional approaches to a preliminary assessment of the innovative projects’ economic efficiency in the field of sustainable development, which, on the one hand, comprise recommendations on calculating the limit value of capital investments, and on the other, suggest a more thorough study of the risk component of the project. The importance of assessing the marginal capital investments in innovative projects can be explained by the uncertainty of the expense portion and the need for a prospective investor to acquire a deep understanding of the project economics, taking into account all possible changes. The article focuses on the methods for assessing the discount rate of innovative projects in consideration with their specific risks, and offers options for analytical and graphical interpretation of the results. The additions proposed by the authors to the conventional approach to assessing economic efficiency appear relevant and practically important for attracting investments in sustainable development projects including the agricultural ones  as they enables a wider assessment of risks, increased transparency and attractiveness of such projects. Beyond developing theoretical approaches to the innovative projects’ assessment in the field of sustainable development, the authors analyze the scientific literature on matters dealt with the study, including investments in sustainable development and an innovative approach to addressing sustainable development challenges. As an example of a project in the field of sustainable development, the authors consider an innovative atmospheric fresh water generator AGVP-1000 (AFWG-1000), which can be used to produce fresh water in any accessible place and with sufficient wind power potential. AGVP-1000 is a resource-saving and eco-friendly technology. The innovation under consideration is strategically important for the development of the agro-industrial complex in water-scarce countries, as it allows generating water for agricultural needs under difficult natural and climatic conditions.
Keywords: Sustainable development; renewable energy; innovative project; project risks; discount rate; investment efficiency.